The existence and stability of relativistic shock waves: general criteria and numerical simulations for a non-convex equation of state - Tytarenko, P.V.; Zhdanov, V.I. (Condensed Matter Physics, 1998)
A small viscosity approach to discontinuous flows is discussed in relativistic
hydrodynamics with a general (possibly, non-convex) equation of state
that typically occurs in the domains of phase transitions. Different forms of
criteria for the existence and stability of relativistic shock waves, such as
evolutionarity conditions, entropy criterion and corrugation stability conditions
are compared with the requirement of the existence of shock viscous
profile. The latter is shown to be most restrictive in case of a single-valued
shock adiabat expressed as a function of pressure. One-dimensional numerical
simulations with artificial viscosity for a simple piecewise-linear
equation of state are carried out to illustrate the criteria in the case of planar
and spherical shock waves. The effect of a phase transition domain on
the shock amplitude in the process of a hydrodynamical spherical collapse
is demonstrated. Обговорюється підхід малої в’язкости до розривних потоків у релятивістичній гідродинаміці із загальним (можливо, неопуклим) рівнянням стану, яке характерне для области фазових переходів. Різні форми критеріїв існування та стійкости релятивістичних ударних хвиль
— умови еволюційности, ентропійний критерій та умови складчастої
стабільности — порівнюються з вимогою існування ударного в’язкісного профілю. Показано, що останній критерій є більш обмежуючим
у випадку ударної адіябати, яка виражається як однозначна функція
тиску. Для ілюстрування цих критеріїв у випадку плоских та сферичних ударних хвиль проведено одновимірне числове моделювання зі
штучною в’язкістю для простого кусково–лінійного рівняння стану.
Продемонстровано вплив области фазових переходів на ударну амплітуду у процесі гідродинамічного сферичного колапсу.